Fabrication of Mn–CeOx/CNTs catalysts by a redox method and their performance in low-temperature NO reduction with NH31. Issue 36 (23rd April 2015) - Zhang, Yanbing; Zheng, Yuying; Wang, Xie; Lu, Xiulian
<x xml:space="preserve">Abstract</x> Highly active Mn–CeOx/CNTs catalysts were first fabricated by a novel redox method, and a formation mechanism was proposed.